2014
DOI: 10.1371/journal.pone.0086045
|View full text |Cite
|
Sign up to set email alerts
|

Ex-PRESS Implantation versus Trabeculectomy in Open-Angle Glaucoma: A Meta-Analysis of Randomized Controlled Clinical Trials

Abstract: ObjectiveTo evaluate the efficacy and safety of Ex-PRESS implantation (Ex-PRESS) compared to trabeculectomy in the treatment of patients with open-angle glaucoma (OAG).MethodsA comprehensive literature search using the Cochrane Methodology Register to identify randomized controlled clinical trials (RCCTs) comparing Ex-PRESS to trabeculectomy in patients with OAG. Efficacy estimates were measured by weighted mean difference (WMD) for the percentage intraocular pressure reduction (IOPR%) from baseline to end-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 20 publications
2
30
0
2
Order By: Relevance
“…When metaanalysis of outcomes is appropriate, pooling across studies should increase the power and yield valuable information. Authors of a few recently published articles have addressed the effectiveness and safety of the Ex-PRESS and Ologen devices (Chen 2014;He 2014;Wang 2013a). However, a comprehensive, rigorous systematic review in this area is warranted.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…When metaanalysis of outcomes is appropriate, pooling across studies should increase the power and yield valuable information. Authors of a few recently published articles have addressed the effectiveness and safety of the Ex-PRESS and Ologen devices (Chen 2014;He 2014;Wang 2013a). However, a comprehensive, rigorous systematic review in this area is warranted.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…EX-PRESS implantation was associated with higher rates of complete operative success and fewer hyphemas compared with trabeculectomy. 63,64 Patel et al 65 also observed no significant different in success rates between the two operations but found the overall 1-year cost was significantly greater for EX-PRESS implantation, and the incremental cost-effectiveness ratio was $9625 (95% confidence interval, $2435-548,084).…”
Section: Introductionmentioning
confidence: 96%
“…Two meta-analyses 63,64 examined the efficacy and safety of EX-PRESS implantation compared with trabeculectomy for uncontrolled POAG (3 of the 4 randomized controlled trials included in each analysis were the same) and found the two interventions to have similar efficacy in IOP reduction. EX-PRESS implantation was associated with higher rates of complete operative success and fewer hyphemas compared with trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…When meta-analysis of outcomes is appropriate, pooling across studies should increase the power and yield valuable information. Authors of a few recently published articles have addressed the effectiveness and safety of the Ex-PRESS and Ologen devices (Chen 2014; He 2014; Wang 2013a). However, a comprehensive, rigorous systematic review in this area is warranted.…”
Section: Introductionmentioning
confidence: 99%